(Applied Study on Private Syrian Commercial Banks)The Effect Of Using The Altman Model To Predict Financial Failure On Loan Portfolio Returns. (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The study aims to apply the financial ratios of the Altman model to predict financial failure on the private Syrian commercial banks listed on the Damascus Stock Exchange, in addition to identifying the impact of using the Altman model on the returns of each bank’s loan portfolios separately, and to achieve this, the necessary data were collected from the published annual reports. There are 11 banks from the official website of the Damascus Securities Exchange, where the study included the years from 2011-2019, and the independent variable was represented by the Altman model and was measured using financial ratios (profitability - liquidity - financial independence - operational efficiency) and the variable dependent on the returns of loan portfolios It was measured through: Loan portfolio rate of return = total interest and commissions from loans/total loans. The results of the study showed that there was no significant, statistically significant effect of Altman’s model on the rate of return on the loan portfolio of the following private commercial banks: (Bank Audi - Syria, Bank Al-Sharq, Arab Bank-Syria, Fransabank-Syria, Bank of Syria and Overseas, Byblos Bank-Syria, International Bank for Trade and Finance, Bank of Syria and Gulf). And there is a positive, significant, and statistically significant effect of the Altman model on the rate of return on the loan portfolio of the following private commercial banks: (Qatar National Bank - Syria, Bank of Jordan - Syria, Bemo Saudi Fransi Bank).